Analisis Perkembangan Digitalisasi Koperasi dalam Upaya Peningkatan Partisipasi Anggota di Koperasi Lapas Kelas IIb Tasikmalaya - Harry Ramdhani Hadianto (Jurnal Bisnis dan Kewirausahaan, 2024)
Tasikmalaya Class IIb Prison Cooperative is a primary cooperative that is included in the type of producer cooperative and has a savings and loan unit. This study aims to determine the development of cooperative digitalization in an effort to increase member participation. The method used in this study is a case study method by describing each dependent variable through data collection with questionnaires and literature studies. Members of the Tasikmalaya Class IIB Prison Cooperative responded positively to digitalization and welcomed the digitalization policy by participating in every activity carried out by the cooperative and always following the information that is spread. This policy is an advantage for the cooperative because if it is realized, the opportunity for the cooperative to compete with other business entities and expand its reach will be even more open. That way, the cooperative's efforts to increase member participation will be more real to be realized. In this study, the development of cooperative digitalization in the Class II B City Prison Cooperative had an average score of 3.41. This shows that the participation of cooperative members in the Class II B City Prison Cooperative is in the category: "Quite Good".